2012
DOI: 10.1002/ajmg.a.35486
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency, centromeric instability, facial anomalies (ICF) syndrome, due to ZBTB24 mutations, presenting with large cerebral cyst

Abstract: The Immunodeficiency, Centromeric instability, Facial anomalies (ICF) syndrome is an autosomal recessive disease presenting with immunodeficiency secondary to hypo- or agammaglobulinemia, developmental delay, and facial anomalies. Centromeric instability is the cytogenetic hallmark of the disorder which results from targeted chromosomal rearrangements related to a genomic methylation defect. We describe a patient carrying a homozygous mutation of the ZBTB24 gene, which has been recently shown to be responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…13 Of twelve ICF2 patients, half had hypogammaglobulinemia, whereas the other half had agammaglobulinemia. IgA was present in (sub)normal levels in seven patients.…”
Section: Infectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…13 Of twelve ICF2 patients, half had hypogammaglobulinemia, whereas the other half had agammaglobulinemia. IgA was present in (sub)normal levels in seven patients.…”
Section: Infectionsmentioning
confidence: 98%
“…12 ICF2 patient 65 had a large cerebral arachnoidal cyst. 13 ICF1 patient 42 had a rod/cone retinal dystrophy. It is unclear whether this was coincidental.…”
Section: Cerebral Malformationsmentioning
confidence: 99%
“…He was only diagnosed with it following the same diagnosis in his sister (who did have many features of ICF syndrome) which prompted investigations in the rest of her family 11. Cerbone et al 12 also describe a patient with ICF syndrome with subclinical immunodeficiency (low IgM) and suggest that ICF syndrome could be more common than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…8 In ICF2, immunoglobulin class deficiencies are less extreme, with one patient in the study of Cerbone et al even having normal serum IgA and IgG levels. 28 Notably, this patient is the only ICF2 case reported to date harboring two missense mutations in ZBTB24; all other ICF2 patients have at least one predicted premature stop codon. Of the other ICF2 patients in Weemaes et al's study, six had normal levels of IgA and/or IgM.…”
Section: Immunological Findingsmentioning
confidence: 98%
“…Follow-up studies identified other ICF2 families with mutation in ZBTB24, supporting this loss-of-function model. 8,27,28 CLINICAL PRESENTATION…”
Section: Zbtb24 (Omim #614069)mentioning
confidence: 99%